Epidemiological, demographic and clinical data on chronic viral hepatitis C in Tuscany. (3rd April 2019) - Stasi, Cristina; Silvestri, Caterina; Berni, Roberto; Rossana Brunetto, Maurizia; Zignego, Anna Linda; Orsini, Cristina; Milani, Stefano; Ricciardi, Liana; De Luca, Andrea; Blanc, Pierluigi; Nencioni, Cesira; Aquilini, Donatella; et al.
Abstract: Background: Recent introduction of direct antiviral agents (DAAs) has completely changed the scenario regarding hepatitis C virus (HCV) treatment. Certain countries' economic health programs prioritize DAAs according to specific clinical features of HCV-infected patients. The aim of this study was to define epidemiological, demographic and clinical characteristics of HCV-infected patients in the Tuscany region of central Italy. Methods: We enrolled HCV patients with chronic viral hepatitis who were referred to the outpatient services of 16 hospitals in Tuscany from 1 January 2015 to 31 December 2015. Case report forms contained patient information including main demographic data, blood chemistry data, viral hepatitis markers, instrumental evaluations (liver biopsy or transient elastometry, liver ultrasound), eligibility for DAAs, and liver transplantation or therapy already in progress. Results: Of all patients considered, 2919 HCV patients were enrolled (mean age: 57.44 ± 15.15; 54% males, 46% females). All routes of transmission were well represented (intravenous drug use in 20.7%; nosocomial/dental care in 20.6%; and coagulation factors/blood transfusions in 13.3%). Diabetes was the highest represented comorbidity (20.8%), followed by metabolic syndrome (15.5%) and ischemic heart disease (6.2%). The most prevalent HCV genotypes were 1b (47.4%) and 2 (16.5%). In the whole cohort of patients, 32.8% were cirrhotic (40 patients were listed for liver transplantation). Signs of portal hypertension were present mostly in the group older than 45 years (92.3%). Extrahepatic HCV-related diseases were present in 13.3% of cases (cryoglobulinemic syndrome in 58.3% and B-cell non-Hodgkin's lymphoma in 10.5%). Conclusions: Our study provides evidence of a high prevalence of epidemiological changes in HCV infection with a major prevalence of advanced liver disease, such as portal hypertension, in this elderly cohort of patients.